1997
DOI: 10.14430/arctic1089
|View full text |Cite
|
Sign up to set email alerts
|

The Final Days of the Franklin Expedition: New Skeletal Evidence

Abstract: ABSTRACT. In 1992, a previously unrecorded site of Sir John Franklin's last expedition (1845 -1848) was discovered on King William Island in the central Canadian Arctic. Artifacts recovered from the site included iron and copper nails, glass, a clay pipe fragment, pieces of fabric and shoe leather, buttons, and a scatter of wood fragments, possibly representing the remains of a lifeboat or sledge. Nearly 400 human bones and bone fragments, representing a minimum of 11 men, were also found at the site. A combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 36 publications
3
55
0
Order By: Relevance
“…The human mandible found in the burial is relatively large, and it and several matching pairs of large bones, including humeri, femora, tibiae, and fibulae, would thus be consistent with the large individual Hobson discovered in the stern of the boat. However, some of the attributes of the NgLj-3 remains-particularly the cut marks-are more difficult to reconcile with the accounts of Hobson and McClintock. Previous studies of skeletal remains from members of the Franklin expedition, including a large collection from site NgLj-2 in Erebus Bay, have revealed cut marks consistent with oral historical reports that Franklin's men had engaged in survival cannibalism Beattie and Savelle, 1983;Keenleyside et al, 1997). The relative frequency of bones exhibiting cut marks is quite low (5%) in the NgLj-3 assemblage, as is the number of elements affected, but the earlier studies have demonstrated that the presence of cut marks would not be surprising in an assemblage of this type from Erebus Bay.…”
Section: Source Of the Assemblagesupporting
confidence: 62%
See 1 more Smart Citation
“…The human mandible found in the burial is relatively large, and it and several matching pairs of large bones, including humeri, femora, tibiae, and fibulae, would thus be consistent with the large individual Hobson discovered in the stern of the boat. However, some of the attributes of the NgLj-3 remains-particularly the cut marks-are more difficult to reconcile with the accounts of Hobson and McClintock. Previous studies of skeletal remains from members of the Franklin expedition, including a large collection from site NgLj-2 in Erebus Bay, have revealed cut marks consistent with oral historical reports that Franklin's men had engaged in survival cannibalism Beattie and Savelle, 1983;Keenleyside et al, 1997). The relative frequency of bones exhibiting cut marks is quite low (5%) in the NgLj-3 assemblage, as is the number of elements affected, but the earlier studies have demonstrated that the presence of cut marks would not be surprising in an assemblage of this type from Erebus Bay.…”
Section: Source Of the Assemblagesupporting
confidence: 62%
“…Therefore, most clinicians do not consider the condition to be abnormal (Barnes, 1994:49). Cleft neural arch was previously documented in an atlas vertebra from NgLj-2 (Keenleyside et al, 1997).…”
Section: Pathological and Non-pathological Featuresmentioning
confidence: 98%
“…Almost immediately Arctic veterans like Richard King and William Parker Snow campaigned for further expeditions, although it was several years before another explorer returned to the King William Island region in search of survivors, tombs, testimony or any paper records. In the late twentieth century, scientists and archaeologists confirmed Inuit accounts of cannibalism (see Beattie and Savelle, 1983;Keenleyside, Bertulli and Fricke, 1997;Potter, 2016), while in the last few years, teams sponsored by the Canadian government launched annual searches for the wrecks of the Erebus and Terror. These proved successful in 2014 and 2016.…”
Section: The Spectral Arcticmentioning
confidence: 99%
“…• Explorer Sir John Franklin and his crew who met their deaths in attempting to find the Northwest Passage in 1847, and some of whom, according to contemporaneous accounts now backed by recent archaeological research, engaged in cannibalism (Irish Times, 'The American Franklin search expedition', 9 October 1880; Keenleyside et al 1997). …”
mentioning
confidence: 99%